Pengaruh Kedisiplinan Belajar Dan Perhatian Orang TuaTerhadap Prestasi Belajar Siswa Kelas Tinggi Sdn Saren 2Tahun Ajaran 2015/2016 - RAHMAWATI, IRMA, Drs. Mulyadi Sri Kamulyan, M.Pd (2016)
The objective of the study is to know the effect of disciplinary toward student achivement, the effect parental care toward student achivement, the effect of disciplinary and parental care toward the effect of disciplinary and parental care toward student high class achivement of SDN Saren 2 2015/2016. This study is included in qualitative descriptive research. The population of this research is all of the high class student (IV, V, VI) SDN Saren 2 2015/2016 as many as 63 students. This research uses systematic sampling as many as 32 students. The data collection technique uses questionaire and documentaions. The data analysis technique uses double linear regression analysis, T test, F test, coeficient determination, SR and SE which firstly with normality test, linearity test, homogenity test. Based on double linear regression analysis it can be obstained equation : Y=45,557+ 0,120 X1 + 0,173 X2.Data analysis result with significance rate 5% obstained : (1) disciplinary of study has significance effect toward student achivement. this is based on T test found that thitung > ttabel, that is 2,673>2,042 with significance < 0,05 that is 0,012 with relative contribution as much as 43,57% and effective contribution as much as 14,4%. (2) Parental care has effect toward student achivement. Based on T test it can be found that thitung > ttabel, that is 2,233>2,042 with significance < 0,05 that is 0,033 relative contribution as much as 56,43% and effective contribution as much as 18,6%. (3) Disciplinary and parental care has effect toward student achivement. Based on F test it can be found that thitung > ttabel, that is 7,152>3,32 with significance < 0,05 that is 0,03. Based on calculation of coeficinence determination result it can be known that the effect of disciplinary and parental care toward student achevement give contribution as much as 33,0% while 67,0% are affected by the others variable which are not observed. Keywords : dicsiplinary study, parental care, and student achivement.